The role of information systems in the digital transformation of palm oil plantations: a systematic literature review - Muhammad Fitrah Sulthon; Lukman Abdurrahman (JRTI (Jurnal Riset Tindakan Indonesia), 2025)
This study examined the role of information systems in supporting digital transformation in oil palm plantations using a systematic literature review (SLR). Despite the increasing adoption of digital technologies, the strategic integration of information systems in plantation management remains limited. The review was conducted by searching three major scientific databases Scopus, Web of Science, and Google Scholar for articles published between 2020 and 2025. A total of 127 articles were initially identified, of which nine studies were selected based on predefined inclusion and exclusion criteria, including relevance to oil palm plantations, focus on information systems, and methodological rigor. The quality of the selected articles was assessed using a structured evaluation framework to ensure reliability. The results showed that 89% of the reviewed studies reported significant improvements in operational efficiency and data accuracy, while 78% highlighted enhanced decision-making supported by information systems. Web-based and integrated systems were the most commonly implemented technologies, appearing in 67% of the studies, particularly for data integration, monitoring, and reporting. However, 56% of the studies identified human resource limitations and 44% reported system integration issues and organizational resistance as major barriers. The study concluded that information systems serve not only as operational tools but also as strategic enablers of sustainable digital transformation in oil palm plantations, emphasizing the need for integrated systems and strong organizational support.